2004
DOI: 10.1016/s0006-3495(04)74216-2
|View full text |Cite
|
Sign up to set email alerts
|

Folding Kinetics and Structure of OEP16

Abstract: The chloroplast outer membrane contains different, specialized pores that are involved in highly specific traffic processes from the cytosol into the chloroplast and vice versa. One representative member of these channels is the outer envelope protein 16 (OEP16), a cation-selective high conductance channel with high selectivity for amino acids. Here we study the mechanism and kinetics of the folding of this membrane protein by fluorescence and circular dichroism spectroscopy, using deletion mutants of the two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 32 publications
(47 reference statements)
2
43
0
Order By: Relevance
“…Furthermore, the OEP16 protein shows sequence and secondary structure similarity to components of the protein translocase of the inner mitochondrial membrane (Tim17, Tim22, and Tim23) and to a lesser extent to LivH, an amino acid transporter in the cytosolic membrane of E. coli (Rassow et al, 1999). Like these membrane transporters, OEP16 forms four a-helical transmembrane domains according to circular dichroism studies ( Figure 2A, Linke et al, 2004). This is rather unusual, since the channel proteins in the outer membranes of mitochondria (VDAC) and Gram-negative bacteria (see above) are exclusively built by b-barrels.…”
Section: Oep16 a Channel Specific For Amino Acids And Aminesmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, the OEP16 protein shows sequence and secondary structure similarity to components of the protein translocase of the inner mitochondrial membrane (Tim17, Tim22, and Tim23) and to a lesser extent to LivH, an amino acid transporter in the cytosolic membrane of E. coli (Rassow et al, 1999). Like these membrane transporters, OEP16 forms four a-helical transmembrane domains according to circular dichroism studies ( Figure 2A, Linke et al, 2004). This is rather unusual, since the channel proteins in the outer membranes of mitochondria (VDAC) and Gram-negative bacteria (see above) are exclusively built by b-barrels.…”
Section: Oep16 a Channel Specific For Amino Acids And Aminesmentioning
confidence: 97%
“…Angemeldet | 129.187.254.47 Heruntergeladen am | 18.11.13 10:46 Linke et al (2004), OEP16 from pea contains four a-helical transmembrane domains. Helices II and IV are determined to be three to five amino acids longer than helices I and III.…”
Section: Bereitgestellt Von | Universitaetsbibliothek Der Lmu Muenchenmentioning
confidence: 99%
“…The even more closely related OM protein OEP16 of chloroplasts probably evolved from Tim22 after it diverged from Tim23/17 (they group on a tree: Rassow et al 1999). OEP16, unlike bacterial OM proteins, is not a b-barrel, but has four membrane-spanning a-helices (Linke et al 2004). It probably evolved from Tim22 by gene duplication and insertion into the OM from the cytosol, another example of recruitment of a pre-existing mitochondrial import component for chloroplast import, as postulated (Cavalier-Smith 1982).…”
Section: Negibacterial Origin Of Tom40 Sam50 and Tim22mentioning
confidence: 99%
“…Subsequent studies on the phylogeny and secondary structure revealed that OEP16 belongs to the superfamily of preprotein and amino acid transporters (PRAT) including the protein translocating channels Tim17, Tim22, and Tim23 of the inner mitochondrial membrane (16,37). Like these transporters, OEP16 forms 4 ␣-helical transmembrane domains (38). In Arabidopsis 3 genes are coding for OEP16 isoforms, named OEP16.1, OEP16.2, and OEP16.4, respectively (16,39).…”
mentioning
confidence: 99%